Evaluation of post-secondary career and technical education courses - Ahad Navidi; Mahmood Barzegar (فصلنامه نوآوری‌های آموزشی, 2012)
To evaluate post-secondary career and technical education courses running by the ministry of education, 2300 students, 793 graduates from 39 academic disciplines, 500 teachers and 121 managers of career and technical education colleges have been selected as research sample, using random sampling method. The required data were collected using questionnaires, interviews and data forms. Quantitative data were processed and analyzed using descriptive statistics  (frequency percentage and ratio) and qualitative data were analyzed using qualitative methods (classification, summarization, combination). The research findings implicitly indicated that there is ambiguity and multiple conflicts in philosophy, main goals, macro policy, strategies and legal status of mentioned career and technical education courses. The implementation of mentioned continuous five years post-secondary course has failed and the separation of its planning and implementation in the form of three and two years postsecondary courses has leaded in great obstacles for coherence and consistency of career and technical education programs. Quantity and quality of human resources, facilities and educational setting of colleges is not satisfactory. Majority of students and graduates’ cognitive and emotional characteristics are not consistent with the expectations of their profession. Unemployment of almost 28% of those who entered such colleges with hope to gain better job as soon as possible, evidently indicates that there is a serious problem. Considering these findings, some recommendations were proposed for reforming planning and implementation of career and technical education and training courses.